Analisis Strategi Pemasaran Produk Madu Kelulut (Heterotrigona itama) PT. Komoditas Alam Indonesia - Luat, Reformasius Juni; Firayanti, Yuni; Marhamah, Marhamah (AKSIOMA : Jurnal Sains Ekonomi dan Edukasi, 2026)
This study aims to analyze the marketing strategy of kelulut honey (Heterotrigona itama) implemented by PT. Komoditas Alam Indonesia (Komalindo), a company engaged in the production and distribution of local honey in West Kalimantan. The focus of this research is the application of the 4P marketing mix product, price, place, and promotion as the main approach to enhance product competitiveness in both local and national markets. The method used is descriptive qualitative, with data collected through in-depth interviews, field observations, and documentation. The results show that PT. Komalindo segments its market through two main brands: madusyaiful, targeting the upper-middle class, and madu Ori, aimed at the lower-middle class. Pricing is adjusted based on seasonal factors and brand value perception. Distribution channels include online marketplaces and local retail outlets. Promotional strategies involve social media marketing, consumer education, and collaboration with influencers. The company has successfully increased sales volume and customer loyalty, despite challenges such as weather-related production fluctuations and competition from adulterated honey products. The 4P strategy has proven effective and adaptive. This research recommends strengthening educational promotions, diversifying products, and expanding distribution as sustainable strategies.